PENGEMBANGAN POTENSI DESA SIAGA AKTIF DAN PENGOLAHAN PERTANIAN DI WILAYAH TERPENCIL DESA NANGA ANSAR SEBAGAI UPAYA PENINGKATAN DERAJAT KESEHATAN MASYARAKAT - Abduh Ridha; Mardjan Mardjan; Hanum Mukti Rahayu (Universitas Muhammadiyah Pontianak, 2017)
West Kalimantan Health Index occupies the 28th rank of 33 Provinces across Indonesia, while Sekadau District ranks 12th out of 14 districts in West Kalimantan. This indicates that the Sekadau Regency is one of the districts that need to be considered for the development of all sectors. Setuntung and Nanga Ansar Village are two farthest and isolated village in Sakadau. The purpose of KKN-PPM implementation in Setuntung and Nanga Ansar Village was empower the community through the development of active 'Desa Siaga' and the economic sector, especially the processing of snakefruit, banana, and fishery as well as the increase of home reading activities. Implementation of activities in June-August 2016. The results showed succesful implementation of activities in health, economic, and education sectors. In helath sector, we succesfully managed an active 'Desa Siaga', formed posyandu cadres, exhibited assistant nutrition classes in infants and pregnant women in posyandu, initiated of family, schools, and households waste processing. In the economic field, we improved agricultural and fisheris productions, namely snakefruit and fishery, catfish nugget, and pekasam. In the field of education, we formed a mini library and its cadres. Therefore, the coorperation among Belitang Government, Setuntung Village, Nanga Ansar Villages, and universities need to establish so that guidance and development of this activity is sustainable. Keywords: society empowerment, remote area, agricultures, fisheries ‘Desa Siaga’ Management